2014
DOI: 10.1117/1.jbo.19.2.027004
|View full text |Cite
|
Sign up to set email alerts
|

Direct identification of clinically relevant bacterial and yeast microcolonies and macrocolonies on solid culture media by Raman spectroscopy

Abstract: Abstract. Decreasing turnaround time is a paramount objective in clinical diagnosis. We evaluated the discrimination power of Raman spectroscopy when analyzing colonies from 80 strains belonging to nine bacterial and one yeast species directly on solid culture medium after 24-h (macrocolonies) and 6-h (microcolonies) incubation. This approach, that minimizes sample preparation and culture time, would allow resuming culture after identification to perform downstream antibiotic susceptibility testing. Correct id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 26 publications
(30 reference statements)
1
39
0
Order By: Relevance
“…The classifications documented in Table 4 [30,32,33,35,36,38,100,118,119] while the majority of protein peaks increase or remain unchanged [36]. These results are supported by the work of Talukder et al [121] who used a quantitative Western immunoblot to determine concentrations of DNA and proteins of E. coli cells through the log and stationary phases.…”
Section: Discrimination Based On Growth Mediamentioning
confidence: 57%
See 4 more Smart Citations
“…The classifications documented in Table 4 [30,32,33,35,36,38,100,118,119] while the majority of protein peaks increase or remain unchanged [36]. These results are supported by the work of Talukder et al [121] who used a quantitative Western immunoblot to determine concentrations of DNA and proteins of E. coli cells through the log and stationary phases.…”
Section: Discrimination Based On Growth Mediamentioning
confidence: 57%
“…Samples were grown in Luria-Bertani broth and growth phase was identified by optical density (OD) measurements. The majority of Raman peaks associated with RNA and DNA decreased as bacteria aged from the log to the stationary phase, which has been seen by many groups [30][31][32][33]35,38,118,119]. Moritz et al [36] also found that protein-related peaks increase or stay the same over the same timeframe.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations